Efektivitas Penggunaan Metode Discovery Learning terhadap Keaktifan Belajar Peserta Didik: (Studi Kasus di Kelas XI MA Al-Manshury Sungai Bakau Besar Laut) - Sumiyati (JURNAL PUSAKA, 2020)
Discovery learning method is to understand concepts, meanings, and relationships through an intuitive process to finally arrive at a conclusion. Discovery occurs when individuals are involved, especially in the use of mental processes to discover some concepts and principles. Discovery is done through observation, classification, measurement, prediction, determination and inference. This process is called the cognitive process, while the discovery itself is the mental process of assimilation concepts and principles in the mind (Budiningsih, 2005, p. 43). This study aims to obtain a learning design using discovery learning methods to increase student learning activity. This research was conducted in MA Al-Manshury Sungai Bakau Besar Lat, the focus of this study was to obtain a learning design using the discovery learning method in order to further increase the learning activity of Al-Manshury students in the Sungai Bakau Besar Laut. The research method used is qualitative and the subject of this research is the students of MA Al-Manshury Sungai Bakau Besar Laut, especially Class XI, totaling 28 people. Keywords: Discovery learning, learning effectiveness, active learning.